A cost-effectiveness analysis of the 13-valent pneumococcal conjugated vaccine and the 23-valent pneumococcal polysaccharide vaccine among Thai older adult - Ngamprasertchai, Thundon; Kositamongkol, Chayanis; Lawpoolsri, Saranath; Rattanaumpawan, Pinyo; Luvira, Viravarn; Chongtrakool, Piriyaporn; Kaewkungwal, Jaranit; Chokephaibulkit, Kulkanya; Phisalprapa, Pochamana (Frontiers in Public Health, 2023)
This study aims to assess the economic impact of introducing the 13-valent pneumococcal conjugate vaccine (PCV13) and 23-valent pneumococcal polysaccharide vaccine (PPSV23) to Thai elderly aged ≥65 years who are healthy or with chronic health conditions and immunocompromised conditions from a societal perspective in order to introduce the vaccine to Thailand’s National Immunization Programme for the elderly. A Markov model was adopted to simulate the natural history and economic outcomes of invasive pneumococcal diseases using updated published sources and Thai databases. We reported analyses as incremental cost-effectiveness ratios (ICER) in USD per quality-adjusted life year (QALY) gained. In addition, sensitivity analyses and budget impact analyses were conducted. The base-case analysis of all interventions (no vaccinations [current standard of care in Thailand], PPSV23, and PCV13) showed that PPSV23 was extendedly dominated by PCV13. Among healthy individuals or those with chronic health conditions, ICER for PCV13 was 233.63 USD/QALY; meanwhile, among individuals with immunocompromised conditions, ICER for PCV13 was 627.24/QALY. PCV13 are economical vaccine for all elderly Thai individuals when compared to all interventions. In the context of Thailand, PCV13 is recommended as the best buy and should be primarily prioritized when both costs and benefits are considered. Also, this model will be beneficial to the two-next generation pneumococcal vaccines implementation in Thailand.